KONSEPSI HADIS DALAM PENAFSIRAN MUHAMMAD HUSEIN ATH-THABATHABA’I DALAM TAFSIR AL-MIZAN - Muhammad Sulton (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2026)
This study examines the biography and exegetical thought of Muhammad Husain ath-Thabathaba’i, with a particular focus on the conception of Hadith in his Tafsir al-Mizan. He was born into a scholarly family deeply rooted in intellectual and spiritual traditions, which shaped his intellectual character from an early age. His formal and religious education began in Tabriz and continued in Najaf, a major center of Islamic learning, where he studied various disciplines such as jurisprudence (fiqh), principles of jurisprudence (usul), philosophy, and mysticism (irfan). His intellectual development was also influenced by the socio-political conditions of Iran during the Pahlavi era, marked by processes of secularization. His major work, Tafsir al-Mizan, employs the method of interpreting the Qur’an through the Qur’an (tafsir al-Qur’an bi al-Qur’an), combined with rational, analytical, and comparative approaches. Within this framework, Hadith is not treated as a primary source, but rather as a supporting tool in understanding Qur’anic verses. Ath-Thabathaba’i adopts a selective approach, accepting mutawatir Hadith while exercising caution toward solitary (zhanni) reports. He also demonstrates a moderate stance by engaging with both Sunni and Shi‘i sources. In his perspective, Hadith includes narrations from the Prophet as well as the Imams of Ahl al-Bayt. The use of Hadith in his exegesis serves to reinforce the meanings derived from the Qur’an, particularly in themes such as imamate, intercession, and ulil amr. Thus, the conception of Hadith in Tafsir al-Mizan is integrative, critical, and remains subordinate to the authority of the Qur’an. Although ath-Thabathaba’i belongs to the Twelver Shi‘i tradition, his moderate engagement with Sunni sources in constructing his Hadith conception indicates that he cannot be characterized as excessive (ghuluw).